2014
DOI: 10.4236/ns.2014.61005
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of the hydro-alcoholic and aqueous extracts of <i>Achillea fragrantissima</i> (Forssk.) grown in Jordan

Abstract: Aqueous and hydro-alcoholic extracts of Achillea fragrantissima L. (Asteraceae) grown in Jordan were screened for their antioxidant, antimicrobial, antiplatelet, anti-proliferative and acetylcholinesterase (AChE) inhibition efficacy. Total phenols and flavonoids were determined colorimetrically. The radical scavenging activities were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical scavenging activity assays. High performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…It is reported that pentylenetetrazole induces seizure by the inhibition of GABA A receptors and is widely used model for absence seizure 22 . The activity of Gaisoom against both PTZ and MES induced convulsions could be due the antioxidant activity of Gaisoom because it has been reported that Achillea fragrantissima exhibited antioxidant activity 9,11 . If we compare Hexane and Chloroform chromatograms have bear a resemblance to each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that pentylenetetrazole induces seizure by the inhibition of GABA A receptors and is widely used model for absence seizure 22 . The activity of Gaisoom against both PTZ and MES induced convulsions could be due the antioxidant activity of Gaisoom because it has been reported that Achillea fragrantissima exhibited antioxidant activity 9,11 . If we compare Hexane and Chloroform chromatograms have bear a resemblance to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Achillea fragrantissima is a medicinal shrub plant that belongs to the Asteraceae family (formerly Compositae) 8 . Achillea fragrantissima is a desert plant that has been used for many years in traditional medicine in the Arabia region for the treatment of respiratory diseases and gastrointestinal disturbances 9 . In Saudi Arabia it is known locally as Gaisoom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also demonstrates the presence of tannins as an important molecule which might be responsible for the observed pharmacological properties. Plants such as Rhazya stricta, Moringa peregrina and Achillea fragrantissima are used in folk medicine for the treatment of various ailments, including chronic and pathogenic diseases like diabetes (Ullah et al, 2015), inflammatory conditions (Ali et al, 1998) and microbial infections (Hammad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…and anticancer activity (Shalaby and Richler, 1964;Ageel, et al, 1989;Barel, et al, 1991;Al-Mustafa and Al-Thunibat, 2008;Soltan and Zaki, 2009;Elmann, et al, 2011;Hazem, et al, 2012;Vitalini, et al, 2013;Alenad, et al, 2013;Hammad, et al, 2014;and Choucry, 2017). Comparison between the essential oils of A. fragrantissima (Forssk.)…”
mentioning
confidence: 99%